The Use of Shoulder Box Media to Improve Children's Abilities in Recognizing Letters and Colors - Khoirun Nisah; Terza Travelancya; Ivonne Hafidlatil Kimori (Journal of Childhood Development, 2024)
This study investigates the effectiveness of using shoulder box media to enhance children's abilities in recognizing letters and colors at RA Nurul Wahid Al-Wahyuni. The research employs a qualitative approach with pre-test and post-test designs. The sample consists of 30 kindergarten students aged 4-6 years old. Data were collected through observation and tests. The results show a significant improvement in children's abilities in recognizing letters and colors after using shoulder box media. The results of the research show that the use of soulder box media can increasechildren’s knowledge. The media used in learning is can active and guided game that fulfills the following elements: by using soulder box media the overall score for children who can guess letters is 7,33 and for children who can recognizing corors is 7,28. This indicates that shoulder box media can be an effective tool for enhancing early childhood education. The findings suggest that incorporating shoulder box media into early childhood education can positively impact children's learning outcomes. The interactive and hands-on nature of shoulder box media likely contributes to its effectiveness in engaging young learners. Additionally, the study highlights the importance of utilizing innovative teaching aids to enhance the learning experience of young children, particularly in the development of foundational skills such as letter and color recognition. Overall, the study underscores the potential of shoulder box media as a valuable tool for educators in enhancing the quality of early childhood education